Perancangan Gedung Mixed Use dengan Pola Co-Living Space dengan Pendekatan Arsitektur Biophilic - Kristianawati Kristianawati (Jurnal Arsitektur Wastu Padma, 2023)
In a big city like Jakarta, integration between residence and workplace is an important need for workers. The concept of 'Co-Living Space', which brings together living quarters with ease of accessibility, is emerging as an innovative solution in urban housing development. This concept not only provides accommodation but also creates a natural atmosphere that improves the quality of life in the city. This article discusses the design of an apartment based on the concept of 'Co-Living Space' in the Golden Triangle area of Setiabudi, focusing on the Biophilic architectural approach. Two main questions are presented: (1) How do I integrate the two functions? and (2) How is it implemented in the context of Biophilic architecture? The results of the discussion show that the design of 'sharing space' is effective for integrating living and working functions. In addition, the harmonious design with the surrounding environment and the adoption of Nusantara architecture confirm the application of the Biophilic concept in this research project.